Designing Device of Touchless Smart Lift using Voice Commands with Method of Speech Recognition based on the Internet of Things to Prevent the Spread of COVID-19 (Journal of Electrical Technology UMY, 2023)
In Indonesia, the number of sufferers who were confirmed positive for COVID-19 as of May 14, 2021 approximately 1,734,285 people. One of the causes of the spread of COVID-19 is indicated by passengers touching the lift push button panels. Based on these problems, a device of touchless Smart Lift was designed using voice commands with the method of speech recognition. This voice command controls hardware using the human voice. Voice commands are part of speech recognition methods. The speech recognition method is very suitable to be applied to controlling a lift, so that lift users can access the intended floor via a smart speaker. From testing the performance of the smart lift, the results obtained were that the infrared temperature sensor distance 5 cm with a temperature of 36.65oC. The fastest response time testing 2.14 seconds. Sensor weight testing 195.5 Kg. Testing the accuracy of voice commands for the first and second floors obtained the best results of 100% and for the third floor 95%. From the results of this research, it is hoped that the smart lift device will be able to reduce the spread of COVID-19 without touching the lift push button panel.